Insight Into Hartoušov Mofette, Czech Republic: Tales by the Fluids - Daskalopoulou, Kyriaki; Woith, Heiko; Zimmer, Martin; Niedermann, Samuel; Barth, Johannes A. C.; Frank, Alexander H.; Vieth-Hillebrand, Andrea; Vlček, Josef; Bağ, Cemile Dilara; Bauz, Ralf (Frontiers in Earth Science, 2021)
The Cheb Basin (Czech Republic) is characterized by emanations of magma-derived gases and repeated occurrences of mid-crustal earthquake swarms with small to intermediate magnitudes (ML < 4.5). Associated intense mantle degassing occurs at the Hartoušov Mofette, a representative site for the Cheb Basin. Here, we performed 14 sampling campaigns between June 2019 and March 2020. Gas samples of fluids ascending in two boreholes (F1, ~28 m depth and F2, ~108 m depth) and from anearby natural mofette were analyzed for their chemical (CO2, N2, O2, Ar, He, CH4, and H2) and isotope compositions (noble gases and CO2). CO2 concentrations were above 99.1 % in most samples, while O2 and N2 were below 0.6 %. Helium ranged from 19 to 34 μmol/mol and CH4 was mostly below 12 μmol/mol. Isotope compositions of helium and carbon in CO2 ranged from 5.39 to 5.86 RA and from -2.4 to -1.3 ‰ versus VPDB, respectively. Solubility differences of the investigated gases resulted in fluctuations of their chemical compositions. These differences were accompanied by observed changes of gas fluxes in the field and at the monitoring station for F1. Variations in solubilities and fluxes also impacted the chemical concentration of the gases and the δ13C values that were also likely influenced by Fischer-Tropsch type reactions. The combination of a) the Bernard ratio, b) CH4/3He distributions, c) P-T conditions, d) heat flow, and e) the sedimentary regime led to the hypothesis that CH4 may be of mixed biogenic and volcanic/geothermal origin with a noticeable atmospheric contribution. The drilling of a third borehole (F3) with a depth of ~238 m in August 2019 has been crucial for providing insights into the complex system of Hartoušov Mofette.